Magnetic ordering and dielectric relaxation in the double perovskite YBaCuFeO5. (1st March 2017) - Lai, Yen-Chung; Du, Chao-Hung; Lai, Chun-Hao; Liang, Yu-Hui; Wang, Chin-Wei; Rule, Kirrily C; Wu, Hung-Cheng; Yang, Hung-Duen; Chen, Wei-Tin; Shu, G J; Chou, F-C
Abstract: Using magnetization, dielectric constant, and neutron diffraction measurements on a high quality single crystal of YBaCuFeO5 (YBCFO), we demonstrate that the crystal shows two antiferromagnetic transitions at T N 1 ∼ 475 K and T N 2 ∼ 175 K, and displays a giant dielectric constant with a characteristic of the dielectric relaxation at T N 2 . It does not show the evidence of the electric polarization for the crystal used for this study. The transition at T N 1 corresponds with a paramagnetic to antiferromagnetic transition with a magnetic propagation vector doubling the unit cell along three crystallographic axes. Upon cooling, at T N 2, the commensurate spin ordering transforms to a spiral magnetic structure with a propagation vector of ( h 2 k 2 l 2 ± δ ), where h, k, and l are odd, and the incommensurability δ is temperature dependent. Around the transition boundary at T N 2, both commensurate and incommensurate spin ordering coexist.